Economical effectiveness comparison between Sabit 1 Teras and motorized palm cutter (Cantas) / Nor Izati Md Nor - Md Nor, Nor Izati (Faculty of Plantation and Agrotechnology, 2018)
In oil palm plantation, harvesting is the important element that needs to be carried out efficiently. Proper harvesting technique, skills and tools are the main element to ensure that the yield can be harvest in maximum numbers. The harvesting tool was designed to ease the harvesting process as well as reduce cost. Nowadays, there are several types of harvesting tools that have been used in oil palm plantation which are conventional sickle, chisel, Motorized Palm Cutter and Sabit 1 Teras. This study focuses on comparing the economical effectiveness between Sabit 1 Teras and Cantas and was conducted at Kedah. The data taken by using these two harvesting tools includes all the economic assessment data needed as well as number of bunches harvested per day, time taken needed to harvest bunches, working endurance of workers in field and economic life of each equipment. The data were analyzed by using cost effectiveness analysis and Independent T-Test. The results from statistical analysis showed that Sabit 1 Teras is more effective in terms of technical and economical compared to Cantas. From the results of this study, it was really recommended for the plantation and smallholders to use Sabit 1 Teras since it will help in saving the cost and achieving higher technical efficiency for the harvesting process.